Monitoring of spine curvatures and posture during pregnancy using surface topography – case study and suggestion of method - Michoński, Jakub; Walesiak, Katarzyna; Pakuła, Anna; Glinkowski, Wojciech; Sitnik, Robert (Scoliosis and spinal disorders, 2016)
Background Low back and pelvic pain is one of the most frequently reported disorders in pregnancy, however etiology and pathology of this problem have not been fully determined. The relationship between back pain experienced during pregnancy and posture remains unclear. It is challenging to measure reliably postural and spinal changes at the time of pregnancy, since most imaging studies cannot be used due to the radiation burden. 3D shape measurement, or surface topography (ST), systems designed for posture evaluation could potentially fill this void. A pilot study was conducted to test the potential of monitoring the change of spine curvatures and posture during pregnancy using surface topography. A single case was studied to test the methodology and preliminarily assess the usefulness of the procedure before performing a randomized trial. The apparatus used in this study was metrologically tested and utilized earlier in scoliosis screening. Case presentation The subject was measured using a custom-made structured light illumination scanner with accuracy of 0.2 mm. Measurement was taken every 2 weeks, between 17th and 37th week of pregnancy, 11 measurements in total. From the measurement the thoracic kyphosis and lumbar lordosis angles, and vertical balance angle were extracted automatically. Custom-written software was used for analysis. Oswestry Low Back Pain Disability Questionnaire (ODI) was done with every measurement. The values were correctly extracted from the measurement. The results were: 50.9 ± 2.4° for kyphosis angle, 58.1 ± 2.1° for lordosis angle and 4.7 ± 1.7° for vertical balance angle. The registered change was 7.4° in kyphosis angle, 8.4° in lordosis angle and 5.5° in vertical balance angle. The calculated ODI values were between moderate disability and severe disability (22 to 58 %). Conclusions This case study presents that surface topography may be suitable for monitoring of spinal curvature and posture change in pregnant women. The ionizing radiation studies are contraindicated during pregnancy. Surface topography data connected with information from pain level questionnaires allows to investigate the connection between changes in posture and back pain.